Sustainable interior design practices as an aspect of brand identity in selected Echostore outlets - Teh, Dennille Ashley T.; Faustino, Johanna Acab. (Quezon City UP College of Home Economics, 2012)
In the field of retail design, sustainability has become an approach viewed in different perspectives wherein some retailers seek to integrate positive environmental impact as a significant part of a store's brand identity. The purpose of this study was to determine how selected ECHOstore outlets' brand identity manifested in its specific sustainable practices. Specifically, it aimed to determine the brand identity components of the retail store as well as the application of sustainable practices involving indoor air quality, resource conservation and material application. This is a qualitative case study that aimed to benefit environmental practitioners, interior designers, and retailers as a contribution to practical knowledge on the advantages of sustainable design in a retail setting. For the intentions of this research, three branches of ECHOstores were chosen through purposive sampling. The methods of interview, observation checklist, and triangulation were used to obtain data. The retail store owner, operations manager, and an interior designer with knowledge in sustainable retail were interviewed. The data gathered from the interview and the observations made were synthesized through paragraph format and presented with photo documentation. The results of the study exemplified that brand identity was strongly reiterated in each of the retail stores. While sustainable design practices of indoor air quality, resource conservation and material application were evident in each store outlet, it was discovered that sustainable design was achieved only to a particular extent. Despite the difficulty of sustainable application in retail, ECHOstore maintains conscious effort to incorporate sustainable design practices at an adequate pace. Conclusive to the performed research, suggested directions for further studies incorporate sourcing of respondents through interior designers engaged in retail, and the conducting of feasibility studies for retail businesses that seek to involve sustainable design as an aspect of brand identity.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Sustainable design -- Philippines -- Metro Manila; Stores, Retail -- Philippines -- Metro Manila